2013
DOI: 10.1242/dmm.011361
|View full text |Cite
|
Sign up to set email alerts
|

Raf-mediated cardiac hypertrophy in adultDrosophila

Abstract: SUMMARYIn response to stress and extracellular signals, the heart undergoes a process called cardiac hypertrophy during which cardiomyocytes increase in size. If untreated, cardiac hypertrophy can progress to overt heart failure that causes significant morbidity and mortality. The identification of molecular signals that cause or modify cardiomyopathies is necessary to understand how the normal heart progresses to cardiac hypertrophy and heart failure. Receptor tyrosine kinase (RTK) signaling is essential for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 48 publications
3
47
1
Order By: Relevance
“…3, A to C). Cardiac-specific expression of hRaf Act causes abnormal cardiomyocyte fiber morphology (9). tinC-GFP –positive cardiomyocytes in hearts dissected from tinC>hRaf Act flies lacked well-defined circumferential fibers, whereas cardiomyocytes in tinC>hRaf Act + yki RNAi flies had partially rescued fiber abnormalities (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…3, A to C). Cardiac-specific expression of hRaf Act causes abnormal cardiomyocyte fiber morphology (9). tinC-GFP –positive cardiomyocytes in hearts dissected from tinC>hRaf Act flies lacked well-defined circumferential fibers, whereas cardiomyocytes in tinC>hRaf Act + yki RNAi flies had partially rescued fiber abnormalities (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cardiac-specific expression of RNAi targeting ERK partially rescued Yki S168A -induced cardiac hypertrophy in flies. We previously found that cardiac-specific expression of ERK RNAi completely rescues Raf Act -induced cardiac hypertrophy (9). Thus, ERK may be involved in the crosstalk between Raf and Yki in the heart, but further studies are required to determine the potential involvement of other kinases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations